(untitled) (Journal of Research Updates in Polymer Science, 2012)
We have developed a new hydrocolloid impression gel to eliminate disinfection process that caused to inaccuracy in dimensions of final mold. At first, the proper sample has been prepared based on recommended formulation in literature as well as trial and errors via experimental works. Formulations prepared by variation amounts of ingredients and also samples prepared by adding nanosilver as an antibacterial agent. Characteristic properties such as tear strength, gel temperature, compressive strength and elastic recovery of prepared hydrocolloid impression gels have been evaluated. The effect of agar, potassium sulfate and di-sodiumtetraborate (Borax) on characteristic properties has been investigated. In addition, role of nanosilver as an antibacterial which can be eliminate disinfecting process, on final properties of gels has been evaluated this work presents the role of ingredient on properties of self disinfecting agar impression gel.